Worker’s Perceptions and Attitudes of Coal-dust Exposure and Health Hazards: Case of a Coal-fired Power Station in Southern Africa - Noko, Lentsoe; Chadyiwa, Martha; Makonese, Tafadzwa (Malaysian Journal of Medicine and Health Sciences, 2022)
Introduction: Exposure to coal dust is one of the major health hazards that result in respiratory problems in the coal industry. Literature on workers’ perceptions of coal dust exposure and its health effects is limited. This study aimed to establish workers’ perceptions and attitudes about coal dust exposure and health hazards. Methods: The study used a descriptive cross-sectional design and stratified sampling approach to select 152 workers from a coal-fired power station. Quantitative data was collected using a structured interviewer-administered questionnaire to solicit information on age, gender, work experience, knowledge and perception, with Chi-square tests used for inferential analysis. The study was conducted at Bulawayo Power Station, Zimbabwe. Results: Respondents between 18 to 39 years were the majority. 72.4% had worked at the coal-fired power station for more than a year. Most respondents were aware of the sources of coal dust, its exposure routes, the frequency of exposure that may result in respiratory problems, health effects and methods of prevention. Most respondents perceived they were exposed to coal dust, which they identified as a significant health hazard; they were at risk of having respiratory difficulties and could be protected from its exposure. There was no correlation between workers’ perception of coal dust exposure and their work experience. Conclusion: Workers were knowledgeable of the health hazards associated with coal dust. Coal dust was perceived as the main health hazard resulting in respiratory complications. The perception was the same among workers with different work experiences